Corporate Social Responsibility (CSR) From Islamic Perspective - Fatahillah, Fatahillah (Journal Research of Social Science, Economics, and Management, 2022)
Islam strongly supports Corporate Social Responsibility (CSR) because it cannot be denied that business causes many social problems, and companies are responsible for solving them. Businesses need various natural resources for business continuity, so companies are responsible for maintaining them. Companies create many social problems, Islam strongly supports corporate social responsibility (CSR), and companies have a responsibility to solve them. This study aims to explain what corporate social responsibility (CSR) is in the perspective of Islamic law. This type of research is normative, namely research that begins with the process of obtaining legal certainty. Islam strongly supports corporate social responsibility (CSR). Based on the research results, it cannot be denied that companies cause many social problems and companies are responsible for solving them. Companies need and are responsible for maintaining various natural resources to continue their business.